A Preliminary Result of Seismoelectric Responses Study on Shallow Fluid-Saturated Layer: Numerical Modeling Using Transfer Function Approach - Alamta Singarimbun; Harry Mahardika; Wahyu Srigutomo; Umar Fauzi (Indonesian Journal of Physics, 2008)
Seismoelectric phenomena occurs when a seismic wave propagating in a fluid-saturated medium and crossing an interface of different fluid-saturated mediums that induces electrical field or cause radiation of an electromagnetic wave where only the electric part is being measured. In this paper, we present our research progress on seismoelectric imaging of shallow fluid-saturated layers. The progress mainly discusses on our finite-difference algorithm which provides an alternative method to simulate seismic wave propagation in fluid saturated porous media generating electric fields through an electrokinetic mechanism called seismoelectric coupling. The target of this numerical simulation is to see whether the seismoelectric responses of coseismic field and interface boundary effect can be image on the seismoelectrogram. The simulation begins with the calculation of seismic displacement by using the classical homogeneous formulation. Next, we calculate the seismoelectric responses using the seismoelectric transfer function. The algorithm is then used to simulate seismoelectric responses created from various conditions of finite-infinite and finite-infinite sand-clay model, surface to downhole and crosshole configurations.